Male rape victimisation on screen - Nagy, Victoria M. (Emerald Publishing Limited, 2023)
Research has established that men are unlikely to report being victimised by sexual assault, often out of feelings of embarrassment, shame, fear, and emasculation. Critically examining how the rape of men and boys is represented in television and film, Male Rape Victimisation on Screen argues how presentations of male sexual assault in popular culture have reinforced rape myths associated with male victimisation, as well as the barriers of toxic masculinity that seethe beneath its surface. Employing a feminist and popular criminology framework, Victoria M. Nagy conducts a comprehensive analysis of a range of both adult and child television programmes and films from the past several decades to reveal how rape myths have pervaded popular culture. Turning to reality and the broader implications this has for men who are and are not victims of sexual violence, Nagy explores how knowledge gained from this research can feed into sexual violence prevention efforts and inform a necessary shift in our cultural mindset. Focusing on the under-researched area of male sexual assault, this book broaches cultural, criminology, gender, film, and media studies to reveal how seemingly harmless humour can infiltrate how we think about violent and victimising behaviours.